On the dynamics of farm size distribution in Finland - Sahal, Devendra (Agricultural and Food Science, 1975)
This study attempts to explain why farm structure in Finland is what it is. The static aspects of size distribution are summarised by means of log-normal distribution and tested with respect to data on more than 500 communes for years 1959 and 1969. As to the dynamic aspects, despite some correlation between percentage growth and size at the beginning of the time period and which is believed to be partly spurious, the observed phenomena do not seem to be incompatible with the proposed version of law of proportionate effect. The latter need not be observed at every point in time.